2006
DOI: 10.1111/j.1945-5100.2006.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and evolution of the IVA meteorite parent body: Clues from pyroxene geochemistry in the Steinbach stony-iron meteorite

Abstract: Abstract-We analyzed the Steinbach IVA stony-iron meteorite using scanning electron microscopy (SEM), electron microprobe analysis (EMPA), laser ablation inductively-coupled-plasma mass spectroscopy (LA-ICP-MS), and modeling techniques. Different and sometimes adjacent low-Ca pyroxene grains have distinct compositions and evidently crystallized at different stages in a chemically evolving system prior to the solidification of metal and troilite. Early crystallizing pyroxene shows evidence for disequilibrium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 71 publications
4
25
0
Order By: Relevance
“…Such a metallic body could contain irons with a large range of cooling rates that are correlated with composition, given that such a body would crystallize inwards with the lowestNi irons forming first on the outside. Ruzicka and Hutson (2006) have also concluded from their study of silicate bearing IVA irons that the IVA parent body was disrupted so that an olivine-rich mantle was lost and that the core crystallized inwards. Yang et al (2007) developed a thermal model for metallic asteroidal bodies and showed that a metallic body 150 km in radius with a silicate mantle less than 1 km in thickness can generate radial variations in cooling rates that match the ranges observed in the IVA irons at 700-400°C and 350°C (see Yang et al (2007) for a full description of the assumptions and calculations).…”
Section: Understanding the Cooling Rate Variation Of The Iva Ironsmentioning
confidence: 93%
See 1 more Smart Citation
“…Such a metallic body could contain irons with a large range of cooling rates that are correlated with composition, given that such a body would crystallize inwards with the lowestNi irons forming first on the outside. Ruzicka and Hutson (2006) have also concluded from their study of silicate bearing IVA irons that the IVA parent body was disrupted so that an olivine-rich mantle was lost and that the core crystallized inwards. Yang et al (2007) developed a thermal model for metallic asteroidal bodies and showed that a metallic body 150 km in radius with a silicate mantle less than 1 km in thickness can generate radial variations in cooling rates that match the ranges observed in the IVA irons at 700-400°C and 350°C (see Yang et al (2007) for a full description of the assumptions and calculations).…”
Section: Understanding the Cooling Rate Variation Of The Iva Ironsmentioning
confidence: 93%
“…(5) suggested that the inverse correlation between bulk Ni and cooling rate was caused by an impact that exposed much of the IVA core to space with negligible silicate insulation, arguing that the core had crystallized inwards so that the lowest-Ni irons were on the outside. (6) Ruzicka and Hutson (2006) suggested a model of a simultaneous endogenic heating and collisional disruption to explain the data for Steinbach and other IVA meteorites.…”
Section: Introductionmentioning
confidence: 96%
“…The hit and run impact model of Asphaug et al (2006) invoked for IVA irons by Ruzicka and Hutson (2006) and Yang et al (2008), allows for several molten metallic bodies to be formed as part of the same impact onto a larger body, thus, irons from different offspring bodies could have very similar chemical/isotopic compositions, but different cooling histories. For this scenario, EET could have been derived from an independent, much smaller body, having a much faster cooling rate.…”
Section: Classification Of Eet 83230mentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) Ruzicka and Hutson (2006) and Wasson et al (2006) developed models for the generation of the IVA parental melt on an L/LL chondrite like parent body, despite some major chemical differences between IVA and L/LL chondrites. With respect to HSE, the IVA parental compositions are broadly similar to the absolute concentrations we calculate for a core that might form in a body with a bulk composition similar to an L or LL chondrite, assuming the mass fraction of the core is 20% of the entire parent body, and using the average L chondrite composition of Wasson and Kallemeyn (1988) for the bulk body (Table 6).…”
Section: Iva Core Composition and Parent Body Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation